New Pseudophyllinae from the Lesser Antilles (Orthoptera: Ensifera: Tettigoniidae) - Hugel, Sylvain; Desutter-Grandcolas, Laure (Zootaxa, 2013)
Two new Cocconitini Brunner von Wattenwyl, 1895 species belonging to Nesonotus Beier, 1960 are described from the Lesser Antilles: Nesonotus caeruloglobus Hugel, n. sp. from Dominica, and Nesonotus vulneratus Hugel, n. sp. from Martinique. The songs of both species are described and elements of biology are given. The taxonomic status of species close to Nesonotus tricornis (Thunberg, 1815) is discussed.